Akuntansi Pameran Seni Rupa (Kajian Pengembangan Ekonomi Kreatif Berbasis Seni Budaya Di Kota Banjarmasin) - Julkawait; Nailiya Nikmah (Indonesian Journal of Applied Accounting and Finance, 2024)
Fine art is one part of the arts and culture-based creative economy. To showcase their creations, artists often display their works in exhibitions organized to attract a diverse audience and allow them to appreciate the exhibited pieces. From an industrial management perspective, art exhibitions, with their various objectives and the involvement of multiple stakeholders, require accounting as an informative and diplomatic tool for making accountable decisions in the management of fine art exhibitions. This study employs a qualitative research approach, focusing on artists who organize fine art exhibitions in Banjarmasin. The findings reveal that fine art exhibitions in Banjarmasin have considerable potential to contribute to the development of the creative economy. However, they require more robust management, particularly in the area of accounting.